PENGARUH PEMUPUKAN DAN JARAK TANAM TERHADAP CIPLUKAN (Physalis sp.) PADA TANAH MASAM - Ramadhan, Bahtiar Ilham; Windriyati, Ratna Dwi Hirma; Rochman, Bagus Nur; Ari, Kurniawati (Institute of Computer Science (IOCS), 2024)
Ciplukan (Physalis sp.) is useful for treating disease problems. The application of plant spacing in cultivation is necessary to reduce competition. The aim of the research was to determine the effect of fertilization and planting distance on ciplukan plants. Ciplukan has strong endurance so it can live in extreme areas such as acid soil. Ciplukan cultivation on acidic land requires intensification of treatment and plant spacing to increase yields. The research used a split plot design method with the use of fertilizer treatment factors, namely without fertilizer (P1), goat manure + mycorrhiza (P2), goat manure + phosphorus (P3) and NPK (P4) and a planting distance of 40x50 cm (J1) and 30x50 cm (J2), and all treatments were repeated 4 times. The experimental results were analyzed using analysis of variance at the 5% level and the Duncan Multiple Range Test. The results of the research show that fertilization and plant spacing can simultaneously increase plant height, number of leaves, fruit weight, number of fruit, wet and dry weight of ciplukan plants. The best treatment combination in P4J1.